2017
DOI: 10.3390/f8090311
|View full text |Cite
|
Sign up to set email alerts
|

Lianas Abundance is Positively Related with the Avian Acoustic Community in Tropical Dry Forests

Abstract: Dry forests are important sources of biodiversity where lianas are highly abundant given their ability to grow during times of drought and as a result of secondary growth processes. Lianas provide food and shelter for fauna such as birds, but there are no studies assessing the influence of liana abundance on birds in dry forests. Here we evaluate the influence of liana abundance on the avian acoustic community in the dry forests of Costa Rica at Santa Rosa National Park. We selected forest sites with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It measures the disparity between the quietest and loudest 1 kHz frequency bins. Again, the BI has been found to be a good predictor of diversity in some studies (Eldridge et al., 2018; Gasc et al, 2017; Hilje et al, 2017; Mitchell et al, 2020) while others have found it to be poor (Fuller et al., 2015; Moreno‐Gómez et al, 2019), although concerns about the limitations of the methodologies used in these studies apply here too. We expect both indices to increase with increasing species richness and species abundance, and for correlations between both abundance and richness with the indices to be strongest in the frequency and time bins that are most dominated by the target taxa (Table 2), particularly diurnal bird species at dawn between 0.3 and 12 kHz and nocturnal taxa at night between 0.3 and 4 kHz.…”
Section: Methodsmentioning
confidence: 78%
“…It measures the disparity between the quietest and loudest 1 kHz frequency bins. Again, the BI has been found to be a good predictor of diversity in some studies (Eldridge et al., 2018; Gasc et al, 2017; Hilje et al, 2017; Mitchell et al, 2020) while others have found it to be poor (Fuller et al., 2015; Moreno‐Gómez et al, 2019), although concerns about the limitations of the methodologies used in these studies apply here too. We expect both indices to increase with increasing species richness and species abundance, and for correlations between both abundance and richness with the indices to be strongest in the frequency and time bins that are most dominated by the target taxa (Table 2), particularly diurnal bird species at dawn between 0.3 and 12 kHz and nocturnal taxa at night between 0.3 and 4 kHz.…”
Section: Methodsmentioning
confidence: 78%
“…Moreover, ACIt f has been used to investigate animal phenology [89,90] and to estimate the effect of anthropogenic noise [91]. This index has also been demonstrated to be a good proxy of richness and diversity of the communities in forest areas [74,92] and marine and freshwater systems [93][94][95]. The graphic representation of ACIt f depicts the acoustic signature.…”
Section: Characteristics Of Acit F and Acif Tmentioning
confidence: 99%
“…Lianas provide perching, lekking, and breeding sites, as well as nest materials and nesting sites for many bird species (Michel et al 2015 b ). Indeed, in an observational study in a dry forest in the Guanacaste province of Costa Rica, Hilje et al (2017) found that bird community diversity increased with increasing liana density.…”
Section: Introductionmentioning
confidence: 99%